SN 2014J in M82: new insights on the spectral diversity of Type Ia supernovae. Issue 1 (23rd August 2018) - Zhang, Kaicheng; Wang, Xiaofeng; Zhang, JuJia; Zhang, Tianmeng; Benetti, S; Elias-Rosa, N; Huang, Fang; Lin, Han; Li, Linyi; Li, Wenxiong; Ochner, P; Pastorello, A; et al.
ABSTRACT: We present extensive spectroscopic observations for one of the closest Type Ia supernovae (SNe Ia), SN 2014J discovered in M82, ranging from 10.4 d before to 473.2 d after B -band maximum light. The diffuse interstellar band features detected in a high-resolution spectrum allow an estimate of line-of-sight extinction as A v ∼ 1.9 ± 0.6 mag. Spectroscopically, SN 2014J can be put into the high-velocity (HV) subgroup in Wang's classification with a velocity of Si ii λ 6355 at maximum light of $v$ 0 = 1.22 ± 0.01 × 10 4 km s −1 but has a low velocity gradient (LVG, following Benetti's classification) of $\dot{v}=41± 2$ km s −1 d −1, which is inconsistent with the trend that HV SNe Ia generally have larger velocity gradients. We find that the HV SNe Ia with LVGs tend to have relatively stronger Si iii (at ∼4400 Å) absorptions in early spectra, larger ratios of S ii λ 5468 to S ii λ 5640, and weaker Si ii 5972 absorptions compared to their counterparts with similar velocities but high velocity gradients. This shows that the HV+LVG subgroup of SNe Ia may have intrinsically higher photospheric temperature, which indicates that their progenitors may experience more complete burning in the explosions relative to the typical HV SNe Ia.